Cognitive psychology: mentalistic or behavioristic? - Spiker, C C (Advances in child development and behavior, 1989)
We have examined the question, is modern cognitive psychology a return to classical structural or functional psychology or does it conform to the methodological behaviorism first advocated by John B. Watson? We began with a brief description of the methods and goals of classical psychology, noting that observations of the mental phenomena were made by highly trained observers who were themselves scientists (or at least, scientists-in-training). These scientists were searching for cross-sectional laws that connected mental elements with complex mental phenomena. Among the primitive terms of these psychologists were some that referred to simple mental events. Classical psychologists failed to reach their goals for empirical reasons; their failure was not due to methodological (logical) inadequacies. We examined methodological behaviorism and found it to have two main principles. The first is that the primitive terms of psychology should refer to the simple properties of, and simple relations among, physical objects and events--the same primitives used in the physical sciences. The second is that psychologists should look for process laws that permit the prediction of future behavior given knowledge of the physiological, environmental, and other behavioral variables. Next, we analyzed the activities of cognitive psychologists. We found that they do not treat their subjects as if they were trained observers. Rather, they consistently employ "catch trials" and other checks on the quality of the subjects' observations. We noted that cognitive psychologists could, but usually do not, provide behaviorally and environmentally based "operational definitions" for many of the mentalistic-sounding terms that they introduce into the psychological language. Many of their terms, however, are introduced through the time-honored use of models. That is, they construct models that are only partially interpreted to the empirical world. Some of the concepts in the model remain uninterpreted, and of these, some appear to refer to the mental phenomena that classical psychologists attempted to study and describe. This latter feature is probably what most misleadingly suggests that modern cognitive psychology is a return to classical structural or functional psychology. Finally, we found that cognitive psychology is not, as many believe, a revolution against methodological behaviorism. It is rather a rebellion against the conditioning-based theories that constrained psychologists to the study of the simpler behavioral phenomena.